Pengembangan Minat Literasi dan Seni Tradisional Anak-Anak di Desa Bocor Kecamatan Buluspesantren Kabupaten Kebumen Menggunakan Sanggar Seni - Haryanto, Ridho Tri; Putri, Arina Kurnia; Purwani, Ani; Istaqimi, Faizuna; Cornelia, Citra; Salimi, Moh (Badranaya: Jurnal Pengabdian Kepada Masyarakat, 2024)
After COVID-19, many children experienced a decline in literacy and traditional arts interests, to overcome this in Leak Village, BANI (Read and Art) Sanggar was formed. This study aims to describe the implementation of Sanggar BANI activities and the results of changes in reading interest and art produced. The data analysis method used is quantitative analysis using the Likert scale. The implementation method used in Sanggar Bani activities is using the POAC (Plan, Organizing, Act, Check) model. Planning includes regional determination, observation, development planning, and activity planning. Organizing includes the distribution of jobdesks to team members. The Act includes the implementation of planned activities. Check includes evaluation of activities that have been carried out. The results of the implementation of Sanggar Bani activities include: 1) the use of the POAC model in the implementation of Sanggar Bani activities which focus on developing the interests of literacy and traditional arts of the children of Leak Village, the implementation of literacy and traditional art interest development activities to the evaluation of these activities, and (2) there is an increase in children's literacy interest from 59% to 81% and an increase in children's traditional art interest from 69% to 84%